THE CONCEPT OF “KHALĪFAH” IN THE QUR’AN AND ITS RELEVANCE AS A LEADER IN ISLAM - Nur Hadi Ihsan; Marheni Br Maha; Alin Safaraz Himam; Ani Nur Fauziah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
Humans have an essential role and function as caliphs on this earth. However, the figure of the caliph as a leader has begun to decline. This is due to the lack of knowledge about a caliph’s nature and the obligations that must be carried out. This library research will explore the concept of caliphs in the plural and singular forms found in the Qur'an based on an analysis of thematic interpretation studies and its relevance as a leader in Islam. The results of this study state that the meaning of the khalifah in the Qur'an can be clarified into three, namely: the meaning of the khalifah as a general leader for all human beings, the meaning of the khalifah as a leader that is specific or addressed to a nation or generations, and the meaning of the caliph which is individual, namely to the Prophet David. In addition, this paper can also provide insight into the values ​​or principles of the Shari'a contained in the meaning of caliph so that it can be a reference and is expected to be a motivation to produce a leader who understands the concept of khalifah and can implement his rights and obligations.